Relationship of HBsAg and Kidney Biopsy Marker with HBV Related Glomerulonephropathy - Rahman, GM Hafizur; Alam, Muhammad Rafiqul; Rahman, Hossain Muhammad Mustafijur; Taslima, Al Asma Ul; Ahmed, Faruque; Sikder, Golam Mahabub (Bangladesh Medical Journal, 2022)
Hepatitis B virus infection is a major public health problem worldwide and it causes not only hepatic diseases but also extra hepatic manifestations particularly HBV-associated Glomerulo- nephritis (GN). HBsAg has been observed in the glomeruli of some patients with glomerulonephritis. HBV related glomerulo- nephritis may be found in HBV seropositive as well as sero- negative patients. HBV may present in the renal tissue of such patients. In most cases detection of HBsAg in the renal tissue by renal biopsy and immunohistochemistry can establish the etiology. To find out the relationship of HBsAg and Kidney biopsy marker with HBV related glomerulonephropathy, this cross sectional study was done in the Department of Nephrology, Bangabandhu Sheikh Mujib Medical University (BSMMU), during the period of July 2015 to June 2016. A total number of 53 cases who fulfilled the inclusion and exclusion criteria were selected as sample. Samples were selected by purposive sampling technique. HBsAg antigen in renal tissue was found in 2 patients among 7 patients who were seropositive for both HBsAg and Anti HBc(total), 2 patients among 8 patients who were HBsAg seronegative but Anti HBc (total) seropositive, 2 patients among 38 patients who were seronegative for both HBsAg and Anti HBc(total). There were no patients in this study who was HBsAg seropositive but Anti HBc (total) seronegative. Total 11.3% (6 patients) of renal biopsy specimens were found to have HBsAg deposits which included 3 cases of Membrano- proliferative GN and one of each of Membranous nephropathy, Mesangial proliferative GN and IgA nephropathy. The high rate of HBsAg deposits found in renal tissue indicates that detection of HBsAg deposition should be done for all histological varieties of GN. Antiviral therapy may be used to stop progression of HBV associated nephropathy. Bangladesh Med J. 2021 Sept; 50(3): 1-6